IMPLEMENTASI KEBIJAKAN SISTEM DATABASE PEMASYARAKATAN PADA LEMBAGA PEMASYARAKATAN KELAS IIA MANADO DIMASA PANDEMI COVID-19 - Hendra Stevi Lumataw; Max ., Rembang; Welly ., Waworundeng (Sam Ratulangi University, 2021)
The purpose of this research is to analyze what causes the implementation of the correctional database system policy at Manado Class IIA Correctional Institution is not optimal. The method used in this research is qualitative with a descriptive case study approach. This research instruments are document study, observation and interviews. The research found that the process of integration rights services for prisoners through the correctional database system is not in accordance with the standard operating procedures set because there are still delays in the process of integration of prisoners. Meanwhile, the correctional database system is not optimal due to the lack of resources for operators, a verification mechanism and approval of the integration program, and synergy between institutions. For this reason, it is necessary to increase the number of operators, the verification and approval mechanisms, it is necessary to share the authority with the regional offices, the availability of adequate budget and facilities.